MECHANICAL PROPERTIES DAN PERILAKU CREEP DAN SHRINKAGE BETON MUTU TINGGI USIA MUDA - , ARNALDO SARMENTO DA SILVA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Development in the field of structure has undergone highly rapid progression with the increasing number of suprastructures, which are and will be built by human, such as high-story building construction, bridge, structure in water, anti-nuclear radiation building, and so on. To meet the need for the quality structures, concretes must have high strength. Such concretes are usually designed for the structures of highway, bridge, building, sea building, and port. In addition to advantages, they have also disadvantages: they can shrink and swell, brittle (not ductail), and with low tensile strength. Due to load and environmental effect, the concretes can show creep and shrinkage phenomenon. creep and shrinkage in the concretes of early age are two factors that can influence the premature cracks of concretes and also affect the durability and performance of structures in the high strength concrete at early age. This study on the mechanical properties and creep and shrinkage behaviors in the high strength concretes at early age used three types of the tested Specimens, i.e. 10 cylinders of 150 mm x 300 mm in size, 5 prisms of 76 mm x 76 mm x 286 mm in size, and 6 cubes of 150 mm x 150 mm dan 150 mm in size. The ratio of mix determined was 1 variation and the additional material of Superplasticizer Sika ViscoFlow 3211N, using the fas of 0.32 and the slump of 20 cm. The objective of the study is to find out compresive strength, elastisity modulus, creep and shrinkage in the concretes of the early age. The results of the study show that the compressive strength value of concretes with the tested objects of cylinders of 1, 2, 4, and 28 days old were 22.94 MPa, 33.39 MPa, 43.01 Mpa, and 56.72 MPa, respectively. Meanwhile, the compressive strength value of concretes with creep that were tested again at 28 days old was 54.04 MPa. The compressive strength value of concrete with the tested object of cubes at 1, 4 and 28 days old were 288.90 kg/cm2 (28.89 MPa), 421 kg/ cm2 (42.10 MPa), and 526.63 kg/cm2 (52.63 MPa), respectively. The elastisity modulus value of concretes with the tested specimens of cylender at 2 days old were 35280.28 MPa and 25709.09 MPa. The high tense value of creep in the tested specimen of HSCCreep 28.1 was 0.000154, while the lowest tense value of creep in the tested spemen of HSCCreep 28.2 was 0.000880. The high tense value of shrinkage in the tested object of S5 was 0.000367, while the lowest in the tested object of S1 was 0.000035.